Pengaruh Perencanaan Sumber Daya Manusia dan Budaya Organisasi Terhadap Kinerja Organisasipada Badan Kepegawaian Daerah Pemkot Malang - Andika Wulan Febriani; Endi Sarwoko; Andi Nu Graha (Jurnal Riset Mahasiswa Manajemen, 2019)
This study aims to determine the effect of human resource planning and organizational culture on organizational performance in the Regional Civil Service Agency (BKD) Malang City Government. The research data was obtained from the results of data processing of respondents' responses with 22 questionnaire statements, the data used were primary data from the Regional Civil Service Agency (BKD) of Malang City Government. The method used is quantitative on the instrument declared valid and reliable so that it is feasible to use the number of respondents used by 48 respondents with a total statement of 22 statements. The technique used is multiple linear regression analysis calculated using SPSS Version 16 for Windows. The results of the study use multiple regression analysis which shows that human resource planning has no effect on organizational performance, organizational culture has a significant effect on organizational performance. Simultaneously human resource planning and organizational culture significantly influence organizational performance.